In the most general form, an Nth order ordinary differential
equation (ODE) of a single-variable function
can be expressed
as
![$\displaystyle f\left(x,y(x),y'(x),y''(x),\cdots,y^{(N)}(x)\right)=0$](img2.svg) |
(1) |
which can be considered as a special case of a partial differential
equation (PDE) for a multi-variable function
:
![$\displaystyle f\left(x_1,\cdots,x_N,y,\frac{\partial y}{\partial x_1},\cdots,\f...
...rtial x_1},\cdots,\frac{\partial^2 y}{\partial x_1\partial x_n},\cdots\right)=0$](img4.svg) |
(2) |
The purpose is to obtain a function
that satisfies the
given differential equation and the boundary conditions
![$\displaystyle y(x)\vert _{x=a}=y(a)=y_a,\;\;\;\;\;\;\;y(x)\vert _{x=b}=y(b)=y_b$](img5.svg) |
(3) |
In the following we will only consider the initial value problem
(IVP), by assuming the independent variable to be time,
, and the
boundary condition becomes an initial condition
.
- An ODE is explicit if it can be written in the following
form:
![$\displaystyle \frac{d^Ny(t)}{dt^N}=y^{(N)}(t) =f(t,y(t),y'(t),y''(t),\cdots,y^{(N-1)}(t))$](img8.svg) |
(4) |
otherwise it is implicit.
- An ODE is a autonomous system if it does not explicitly
depend on the independent variable
, i.e., it can be written in
the following form:
![$\displaystyle \frac{d^Ny(t)}{dt^N}=y^{(N)}(t) =f(y(t),y'(t),y''(t),\cdots,y^{(N-1)}(t))$](img10.svg) |
(5) |
- An ODE is linear if it can be expressed as:
![$\displaystyle \sum_{n=0}^N a_i(t) y^{(n)}(t)=\sum_{n=0}^N a_n(t) \frac{d^ny(t)}{dt^n}=x(t)$](img11.svg) |
(6) |
Typically this equation describes the behavior of a linear system
of which the output
is to be determined as the system's
response to a given input
on the right-hand side of the
equation, symbolically represented as
![$\displaystyle y(t)= {\cal T} [ x(t) ]$](img14.svg) |
(7) |
- A linear ODE is a homogeneous equation if the input
on the right-hand side is zero.
- A linear ODE is called a linear constant-coefficient
ODE (LCCODE) if all coefficients
are constants:
![$\displaystyle \sum_{n=0}^N a_i y^{(n)}(t) =\sum_{n=0}^N a_n\frac{d^ny(t)}{dt^n}=x(t)$](img17.svg) |
(8) |
Without loss of generality, we typically assume
.
This N-th order LCCODE describes the behavior of a linear system in
terms of how its output
is related to the input
,
symbolically represented by:
We now only consider solving an Nth order LCCODE in the following cases:
- Homogeneous case with
:
We assume the output takes the form of a complex exponential
and substitute it together with its derivatives
into the equation and get
![$\displaystyle \sum_{n=0}^N a_i y^{(n)}(t) =\left(\sum_{n=0}^N a_n s^n\right) c\,e^{st}=0$](img21.svg) |
(9) |
Dividing both sides by
, we get the characteristic
equation
, which has in general
roots
satisfying
![$\displaystyle \sum_{n=0}^N a_n s^n=\prod_{n=1}^N (s-s_n)=0$](img25.svg) |
(10) |
The general homogeneous solution is therefore a linear combination
of
such solutions
:
![$\displaystyle y_h(t)=\sum_{n=1}^N c_n e^{s_nt}$](img27.svg) |
(11) |
and its kth-order derivatives are
![$\displaystyle y^{(k)}(t)=\frac{d^k}{dt^k}\left(\sum_{n=1}^N c_n e^{s_nt}\right)...
...}{dt^k}e^{s_nt}
=\sum_{n=1}^N c_n s_n^k e^{s_nt} \;\;\;\;\;\;\;(k=0,\cdots,N-1)$](img28.svg) |
(12) |
The
coefficients
can be determined based
on
initial conditions
.
We evaluate
and its derivatives given above at
and
equate them to the corresponding initial values to get
![$\displaystyle y^{(k)}(0)=\sum_{n=1}^N c_n s_n^k =y^{(k)}_0\;\;\;\;\;\;\;(k=0,\cdots,N-1)$](img33.svg) |
(13) |
which can be written in matrix form:
![$\displaystyle {\bf Sc}
=\left[\begin{array}{cccc}1&1&\cdots&1\\ s_1&s_2&\cdots&...
...[\begin{array}{c}y_0\\ y'_0\\ \vdots\\ y_0^{(N-1)}\end{array}\right]
={\bf y}_0$](img34.svg) |
(14) |
Solving this system we get the coefficients
in
.
- Non-Homogeneous case with complex expenential input
:
We assume the output is
, and substitute its
nth-order derivatives
![$\displaystyle \frac{d^n}{dt^n} y(t)= c (j\omega)^n e^{j\omega t},\;\;\;\;\;(n=0,\cdots,N)$](img38.svg) |
(15) |
into the equation, and get
![$\displaystyle \sum_{n=0}^N a_n c (j\omega)^n e^{j\omega t} = e^{j\omega t}$](img39.svg) |
(16) |
Dividing both sides by
and solving for
we get
![$\displaystyle c=\frac{1}{\sum_{n=0}^N a_n (j\omega)^n}$](img42.svg) |
(17) |
and the solution can be found to be
![$\displaystyle y(t)={\cal T} [x(t)]={\cal T} [e^{j\omega t}]
=c e^{j\omega t}=\frac{e^{j\omega t}}{\sum_{n=0}^N a_n(j\omega)^n}$](img43.svg) |
(18) |
- Non-Homogeneous case with periodic input
:
The Fourier series expansion of the periodic input
is
![$\displaystyle x(t)=\sum_{k=-\infty}^\infty X_k e^{jk\omega t}$](img46.svg) |
(19) |
where
and
is the kth Fourier coefficient:
![$\displaystyle X_k={\cal F}[ x(t) ]=\frac{1}{T}\int_T x(t) e^{-jk\omega t}\;dt$](img49.svg) |
(20) |
Based on the previous result, we know that the response to the
kth frequency component
of
is
![$\displaystyle {\cal T} [e^{jk\omega t}]
=\frac{e^{jk\omega t}}{\sum_{n=0}^N a_n(jk\omega)^n}$](img51.svg) |
(21) |
and the total response of this linear system to
is simply
the linear combination of these responses:
where
is the kth Fourier coefficient of
:
![$\displaystyle Y_k=\frac{X_k}{\sum_{n=0}^N a_n(jk\omega)^n}$](img57.svg) |
(22) |
- Non-Homogeneous case with impulse input
:
The Fourier coefficients of the impulse input are
![$\displaystyle X_k=\frac{1}{T}\int_T \delta(t) e^{-jk\omega_kt} dt=1\;\;\;\;\;\;(-\infty<k<\infty)$](img59.svg) |
(23) |
and the output is the impulse response function:
![$\displaystyle y(t)=h(t)={\cal T}[\delta(t)]
=\sum_{k=-\infty}^\infty \frac{1}{\...
...0}^N a_n(jk\omega)^n}e^{jk\omega t}
=\sum_{k=-\infty}^\infty H_k e^{jk\omega t}$](img60.svg) |
(24) |
where
is the frequency response function:
![$\displaystyle H_k=H(j\omega)=\frac{1}{\sum_{n=0}^N a_n (jk\omega)^n}$](img62.svg) |
(25) |
Now the general response given above can be written as
where
.
The Nth order LCCODE can also be solved by the method of Laplace
transform, similar to the Fourier transform method discussed above.
Specifically, we take the Laplace transform on both sides and get
Solving for
we get
![$\displaystyle Y(s)=\frac{X(s)+\sum_{n=1}^N a_n \sum_{i=1}^n s^{n-i}y^{(i-1)}(0)...
...{X(s)+\sum_{n=1}^N a_n \sum_{i=1}^n s^{n-i}y^{(i-1)}(0)}{\prod_{n=1}^N (s-s_n)}$](img69.svg) |
(27) |
and the general solution is
![$\displaystyle y(t)={\cal L}^{-1}[ Y(s) ]$](img70.svg) |
(28) |
Now consider some special cases:
- Homogeneous case:
Given a zero input
with
, we get the homogeneous
solution
![$\displaystyle y_h(t)={\cal L}^{-1}[ Y_h(s) ]
={\cal L}^{-1}\left[ \frac{\sum_{n=1}^N a_n \sum_{i=1}^n
s^{n-i}y^{(i-1)}(0)}{\prod_{n=1}^N (s-s_n)}
\right]$](img72.svg) |
(29) |
Taking partial fraction expansion of
:
![$\displaystyle Y_h(s)=\frac{\sum_{n=1}^N a_n \sum_{i=1}^n s^{n-i}y^{(i-1)}(0)}{\prod_{n=1}^N (s-s_n)}
=\sum_{n=1}^N \frac{c_n}{s-s_n}$](img74.svg) |
(30) |
we get
![$\displaystyle y_h(t)={\cal L}^{-1}\left( \sum_{n=1}^N \frac{c_n}{s-s_n}\right)
...
...n=1}^N {\cal L}^{-1}\left( \frac{c_n}{s-s_n} \right)
=\sum_{n=1}^N c_n e^{s_nt}$](img75.svg) |
(31) |
- Non-homogeneous case with an impulse input:
Given
with
, we
get the output, the impulse response
in time domain,
and the transfer function
in s-domain.
For convenience, we assume zero initial conditions
, so that the transfer function
can be written as:
![$\displaystyle H(s)=Y(s)=\frac{1}{\sum_{n=0}^N a_ns^n}=\prod_{n=1}^N \frac{1}{s-s_n}$](img80.svg) |
(32) |
Based on the convolution theorem, we get the
impulse response function as the convolution of all
function
:
![$\displaystyle h(t)={\cal L}^{-1}[ H(s) ]={\cal L}^{-1}\left[ \prod_{n=1}^N \frac{1}{s-s_n} \right]
=e^{s_1t}*e^{s_2t}*\cdots *e^{s_Nt}$](img82.svg) |
(33) |
Alternatively, we can also take partial fraction expansion of
:
![$\displaystyle H(s)=\frac{1}{\prod_{n=1}^N (s-s_n)}=\sum_{n=1}^N\frac{c_n}{s-s_n}$](img84.svg) |
(34) |
and get the impulse response function:
![$\displaystyle h(t)={\cal L}^{-1} [ H(s) ]
=\sum_{n=1}^N c_n {\cal L}^{-1}\left[ \frac{1}{s-s_n} \right]
=\sum_{n=1}^N c_n e^{s_n t}$](img85.svg) |
(35) |
- Non-homogeneous case with a general input:
Given the impulse response
, we can get the particular
solution corresponding to a general input
:
![$\displaystyle y_p(t)=x(t)\,*\,h(t)=x(t)*e^{s_1t}*e^{s_2t}*\cdots *e^{s_Nt}
=\in...
...x(t-\tau) h(\tau)\;d\tau
=\sum_{n=1}^N c_n \int_0^t x(t-\tau) e^{s_n\tau} d\tau$](img87.svg) |
(36) |